2019
DOI: 10.1002/fsn3.1172
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of surimi and fish nuggets from Queen fish (Scomberoides commersonnianus)

Abstract: The purpose of this study was formulation and evaluation of physicochemical properties of fish and surimi nuggets prepared from Queen fish (Scomberiodes commersonnianus) during 90 days of storage. Chemical analysis showed that surimi nuggets contained less protein, fat, and ash due to washing steps during surimi preparation. The titratable acidity, peroxide, and TBA values for fish nuggets were significantly higher than surimi nuggets during frozen storage (p < .05). Moreover, the textural properties of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Results revealed that the PV of cooked samples increased with storage time, reaching 4.30 meq/kg fat in oven-baked nuggets and 4.03 meq/kg fat in deep-fried nuggets after 90 days. Findings from Moosavi-Nasab et al [ 9 ] also demonstrated an increase in PV in fried fish nuggets, ranging from 1.54 to 4.34 meq/kg fat as the frozen storage period increased up to 90 days. The current study is consistent with previous studies that deep-fried nuggets had relatively lower PV than oven-baked nuggets.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Results revealed that the PV of cooked samples increased with storage time, reaching 4.30 meq/kg fat in oven-baked nuggets and 4.03 meq/kg fat in deep-fried nuggets after 90 days. Findings from Moosavi-Nasab et al [ 9 ] also demonstrated an increase in PV in fried fish nuggets, ranging from 1.54 to 4.34 meq/kg fat as the frozen storage period increased up to 90 days. The current study is consistent with previous studies that deep-fried nuggets had relatively lower PV than oven-baked nuggets.…”
Section: Resultsmentioning
confidence: 86%
“…As a result, the use of good manufacturing practices (GMP) and good hygiene practices (GHP) is recommended. The hygienic handling can lower the initial microbial load [ 9 ]. Furthermore, the reduction in the microbial count may be due to the effect of freezing [ 9 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kind of fish as surimi materials did not affect the TPC. The initial microbial count of the samples significantly influenced by the cleanliness of the fish handling and surimi preparation (Moosavi-Nasab et al, 2019).…”
Section: Microbial Analysismentioning
confidence: 99%